Davis's quick clips : therapeutic exercise - Wilder, J. Nathan (Philadelphia, PA : F. A. Davis Co, 2012)
These technique-oriented demonstrations show you how to assist with exercises post injury to increase strength andimprove range of motion and joint mobilization in your clients
1 13
Keywords: Exercise Therapy -- methods; Physical education and training